2001
DOI: 10.1111/j.1749-6632.2001.tb05640.x
|View full text |Cite
|
Sign up to set email alerts
|

Increases of Mitochondrial Mass and Mitochondrial Genome in Association with Enhanced Oxidative Stress in Human Cells Harboring 4,977 BP‐Deleted Mitochondrial DNA

Abstract: In order to investigate the effect of aging-and disease-associated deletion of mtDNA on cellular functions, we used cytoplasm fusion to construct a series of the cybrids harboring varying proportions of mtDNA with 4,977 bp deletion from skin fibroblasts of a patient with chronic progressive external ophthalmoplegia. The cybrids were grown in the Dulbecco's modified Eagle medium supplemented with 5% fetal bovine serum, 100 g/ml pyruvate and 50 g/ml uridine. The population doubling time was longer for the cybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 46 publications
5
54
0
Order By: Relevance
“…Mitochondrial alterations have long been suspected as contributes to carcinogenesis (16). Previous studies showed that the increased mtDNA in human cells harboring 4,977 bp deleted mtDNA in response to oxidative stress (17). In addition, mitochondrial genomic mutations have been found in HNSC (11).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial alterations have long been suspected as contributes to carcinogenesis (16). Previous studies showed that the increased mtDNA in human cells harboring 4,977 bp deleted mtDNA in response to oxidative stress (17). In addition, mitochondrial genomic mutations have been found in HNSC (11).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the very strong inhibition of many subunits of the ubiquitin-proteasome system is likely a consequence of misfolded and damaged mitochondrial proteins specified by the mtDNA deletions. Also, recent studies have demonstrated that mtDNA deletions increase ROS production, which would seem to compound the misfolding/damage problem [31]. To test these ideas, we measured oxidative damage to proteins by the Oxyblot method, and observed a >300% increase in oxidized proteins.…”
Section: Deletions Inhibit the Ubiquitin And Proteasome Systemmentioning
confidence: 97%
“…Because ZDV has been reported to cause significant mitochondrial toxicity in different in vitro models (23), this may reflect a compensatory response to mitochondrial dysfunction caused by a different pathway. Importantly, an increase in mtDNA does not necessarily mean an increase in mitochondrial function; several studies have shown inhibition of the respiratory function by NRTIs independently through mtDNA polymerase ␥ (29), oxidative stress (26), and increases in mtDNA levels and mitochondrial mass by oxidative stress (27,51). In addition, treatment with NRTIs, including 3TC, abacavir, emtricitabine, and tenofovir, which are known to be less toxic to mitochondria, have been shown to result in increases in mtDNA levels in HepG2 cells (20), human skeletal muscle cells (2), and lymphoblasts (40).…”
Section: Discussionmentioning
confidence: 99%